Alvimopan: a peripheral acting µµ-opioid-receptor antagonist used for the treatment of postoperative ileus. Issue 5 (September 2007) - Balsama, Louis; Weese, James
Alvimopan is a peripherally acting µµ-opioid-receptor antagonist that has been investigated for the treatment of postoperative ileus. Postoperative ileus, defined as a disruption in normal bowel motility, is a significant cause of morbidity and increased hospital costs for the surgical patient. The etiology of postoperative ileus is multifactorial and includes neurogenic, inflammatory and pharmacologic influences. Until this point, there has been no successful pharmacotherapy to treat bowel hypomotility following abdominal surgery. Alvimopan blocks the negative effects of opioids in the gastrointestinal tract without compromising central opioid-based analgesia. Alvimopan has been shown to significantly decrease the effect of narcotics on bowel function, hasten the return of bowel function and decrease hospital stay in the postsurgical patient, without affecting the analgesic effect of opioids. Alvimopan, at the time of writing, is not yet available for general use and is awaiting FDA approval. Currently, there is no FDA-approved pharmacologic agent for the treatment of postoperative ileus.